Legal Responsibility of Debtors for Late Repayment of Loans on the Shopee Application: Perspective of OJK Regulation No.10/PJOK.05/2022 on Information Technology-Based Joint Funding Services - Fransiska Sinaga; Debora; Jinner Sidauruk (Journal of Legal and Cultural Analytics, 2025)
This study aims to understand the legal protection and legal responsibility of debtors in online loan agreements on the Shopee platform. This research is a type of normative juridical legal research, using a legislative approach, a conceptual approach, and a sociological approach. The results of this study are as follows: First, the legal protection provided to debtors of Shopee's Peer-to-Peer Lending (P2PL) loans, regulated by OJK, includes regulations governing peer-to-peer lending services, as outlined in Article 41 of PJOK Number 10/POJK 2022. Second, the debtor's responsibility for late loan payments on Shopee is to pay a fine of 5% of the total bill and record a default in the financial information system, which makes it more difficult to access future loans. If the delay continues, Shopee can freeze the debtor's account and involve a debt collector for collection.